THE INFLUENCE OF WORKLOAD AND WORK ENVIRONMENT ON WORK FATIGUE IN GRAMEDIA TERNATE BOOKSHOP EMPLOYEES - Fadilah Hasan; Rahmat Sabuhari; Ikrima M Mustafa (UIN Raden Mas Said Surakarta, 2024)
This study aims to determine the effect of workload and work environment on fatigue i. This research is a quantitative research. The population in this study were all employees at the Gramedia Bookstore Ternate, using a census study sampling method. The analysis technique used in this study was using multiple linear regression analysis , f test and t test with the help of the SPSS 23 version of the IBN application. The results of this study indicate that: (1) Workload has a positive and significant effect on Work Fatigue, (2) Work Environment has a positive and significant effect on Work Fatigue, (3) Workload and Work Environment have a positive and significant effect on Work Fatigue. Keywords: Workload, Work Environment and Work Fatigue